PENGEMBANGAN MEDIA PEMBELAJARAN VIDEO ANIMASI BERBASIS WAWASAN KEBANGSAAN PADA MATA PELAJARAN PENDIDIKAN PANCASILA KELAS III SDN KADEMANGAN 2 - Robby Adi Wardana; Didit Yulian Kasdriyanto; Shofia Hattarina (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study focuses on the development of animated video media to overcome the obstacles faced by Class III students of SDN Kademangan 2 in understanding Pancasila education materials. The learning media that have been used so far are less effective, making students bored. This study aims to create an interesting and interactive learning experience through animated video media. This study uses the Research and Development (R&D) method, specifically using the Borg and Gall development model which consists of six stages. The media and materials developed have been validated by appointed experts, including media, material, and learning experts, before being tested. The results of the study on class 3 students, namely animated video learning media, are very effective and very valid, as they get a score of 91% for media experts and 80% for material experts. The analysis of teacher responses produced a score of 95%. And there was a significant increase in student test scores from an average pretest score of 65.6 to an average posttest score of 97.3 after using learning media.